2023
DOI: 10.1002/adma.202305648
|View full text |Cite
|
Sign up to set email alerts
|

Ambient‐Stable 2D Dion–Jacobson Phase Tin Halide Perovskite Field‐Effect Transistors with Mobility over 1.6 Cm2 V−1 s−1

Xincan Qiu,
Jiangnan Xia,
Yu Liu
et al.

Abstract: Solution‐processed metal halide perovskites hold immense potential for the advancement of next‐generation field‐effect transistors (FETs). However, the instability of perovskite‐based transistors has impeded their progress and practical applications. Here, ambient‐stable high‐performance FETs based on 2D Dion–Jacobson phase tin halide perovskite BDASnI4, which has high film quality and excellent electrical properties, are reported. The perovskite channels are established by engineering the film crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
11
2
Order By: Relevance
“…The N⋯N distance is the minimum in the case of (1,4-BDA)SnBr 6 and the maximum in (1,4-BDA)SnI 4 . We also note that the interlayer gaps for (1,4-BDA)SnBr 4 (9.549 Å) and (1,4-BDA)SnI 4 (10.183 Å) are slightly different from those reported based on thin film powder X-ray diffraction studies, which are 10.0 Å 27 and 9.7 Å, 28 respectively, wherein the 1,4-BDA conformation was assumed to be all- anti . However, these miniscule differences are common between the bulk and thin film X-ray data due to the differences in sample crystallinity, substrate induced strain and compositional gradient.…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…The N⋯N distance is the minimum in the case of (1,4-BDA)SnBr 6 and the maximum in (1,4-BDA)SnI 4 . We also note that the interlayer gaps for (1,4-BDA)SnBr 4 (9.549 Å) and (1,4-BDA)SnI 4 (10.183 Å) are slightly different from those reported based on thin film powder X-ray diffraction studies, which are 10.0 Å 27 and 9.7 Å, 28 respectively, wherein the 1,4-BDA conformation was assumed to be all- anti . However, these miniscule differences are common between the bulk and thin film X-ray data due to the differences in sample crystallinity, substrate induced strain and compositional gradient.…”
contrasting
confidence: 69%
“…32,43 Furthermore, the bandgap and the emission band positions of (1,4-BDA)SnI 4 are slightly red-shifted when compared with the values reported for thin films. 28,40 We have also observed spectral broadening of the PL spectra of (1,4-BDA)SnI 4 , probably due to defects created during solvent based hydrothermal synthesis. 44…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The strong coordination ability of DMSO is expected to reduce the nucleation rate of perovskite crystals due to the presence of pre-nucleation. 13 The boiling point is another key parameter to determine the evaporation rate of the solvent and should be considered when mixing with DFM. It is generally believed that polar DMSO with high boiling point of 189 °C is less volatile and can readily remain in the perovskite film even after thermal annealing.…”
Section: Resultsmentioning
confidence: 99%
“…Field-effect transistors (FETs) provide a versatile platform to investigate the charge carrier transport of perovskite semiconductors. 12,13 Recent studies have shown that chemical tuning of organic cations offers a simple but effective way to modulate the device performance of 2D perovskite optoelectronics. 14,15 Based on the rapid development of perovskite solar cells by molecular engineering of the spacer cations, the wide compositional space for organic ligands potentially serves as an effective tool to fine tune the charge transport properties in FET devices.…”
Section: Introductionmentioning
confidence: 99%